Development of Canva-Based Interactive Teaching Materials to Enhance Students' Critical Thinking Skills in Fiqh Learning at Islamic High School - Pulungan, Ellly Damayanti; Ananda, Rusydi; Rifa'i, Muhammad; Mousthofa, Ebaa (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This project aims to promote critical thinking abilities among eleventh-grade students in the Social Sciences curriculum at MAN 1 Medan during Fiqh (Islamic Jurisprudence) studying, leveraging interactive teaching materials based on Canva that have been designed. This research uses Research and Development (R&D). The 4-D research design, which consists of four stages—define, design, develop, and disseminate—is used in this study's instructional material development. Thirty-three eleventh-grade Social Sciences students make up the research subjects. The interactive teaching materials based on Canva are highly valid based on the research and development findings. This is supported by the material validation score of 3.07, the subject matter expert assessment score of 3.23, and the language expert validation score of 3.30. The overall recapitulation score of 3.2 further confirms this conclusion. This suggests that the interactive educational resources created by Canva meet appropriate standards and can be utilized by educators and learners alike.